Functional Characterization of a Putative Glycine max ELF4 in Transgenic Arabidopsis and Its Role during Flowering Control - Marcolino-Gomes, Juliana; Nakayama, Thiago J.; Molinari, Hugo B. C.; Basso, Marcos F.; Henning, Liliane M. M.; Fuganti-Pagliarini, Renata; Harmon, Frank G.; Nepomuceno, Alexandre L. (Frontiers in Plant Science, 2017)
Flowering is an important trait in major crops like soybean due to its direct relation to grain production. The circadian clock mediates the perception of seasonal changes in day length and temperature to modulate flowering time. The circadian clock gene EARLY FLOWERING 4 (ELF4) was identified in Arabidopsis thaliana and is believed to play a key role in the integration of photoperiod, circadian regulation and flowering. The molecular circuitry that comprises the circadian clock and flowering control in soybeans is just beginning to be understood. To date, insufficient information regarding the soybean negative flowering regulators exist, and the biological function of the soybean ELF4 (GmELF4) remains unknown. Here, we investigate the ELF4 family members in soybean and functionally characterize a GmELF4 homologous gene. The constitutive overexpression of GmELF4 delayed flowering in Arabidopsis, showing the ELF4 functional conservation among plants as part of the flowering control machinery. We also show that GmELF4 alters the expression of Arabidopsis key flowering time genes (AtCO and AtFT), and this down-regulation is the likely cause of flowering delay phenotypes. Furthermore, we identified the GmELF4 network genes to infer the participation of GmELF4 in soybeans. The data generated in this study provide original insights for comprehending the role of the soybean circadian clock ELF4 gene as a negative flowering controller.